Makerere University-Uganda Heart Institute collaborative cardiovascular disease training and research since 1988. - Okello, Emmy; Ssemogerere, Lameck; Ssinabulya, Isaac; Kayima, James; Nakanjako, Damalie; Sebatta, Elias; Lubega, Sulaiman; Oketcho, Michael; Mwambu, Tom; Lwabi, Peter; Mijumbi, Cephas; Omagino, John (African Health Sciences, 2022)
Background: Makerere University College of Health Sciences has been collaborating with the Uganda Heart Institute to build capacity for research, training and clinical care in cardiovascular medicine for the last 34 years to appropriately respond to rising societal needs for advanced cardiovascular care which was lacking before this period. Aim: To describe the major milestones in the MakCHS-UHI cardiovascular training collaboration and chart way for future collaborations. Method: This short communication highlights some of the salient features and important milestones in the collaboration journey of the two institutions. Conclusion: Clinical centres of excellence in specialised fields of health care, such as the Uganda Heart Institute for Cardiology, provide a conducive academic environment for MakCHS clinical scientists to provide high quality evidence-based care to meet societal needs.
Keywords: Cardiology training; Cardiovascular research; Makerere University College of Health Sciences; Uganda Heart Institute